2023
DOI: 10.3390/agronomy13092292
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship between Cultivar, Endophyte and Environment on the Expression of Persistence in Perennial Ryegrass Populations Using High-Throughput Phenotyping

Chinthaka Jayasinghe,
Joe Jacobs,
Anna Thomson
et al.

Abstract: Perennial ryegrass (Lolium perenne L.) is a commonly grown pasture species in temperate agriculture, mainly serving as a primary energy source for dairy cows. However, its limited persistence often leads to missed production potential and early resowing, especially in countries that experience summer drought, e.g., Australia and New Zealand. Therefore, understanding the factors influencing perennial ryegrass pasture persistence is crucial for sustainable land management and climate resilience in pasture-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…(1) The management and utilization of traditional grasslands [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Overview Of the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…(1) The management and utilization of traditional grasslands [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…This finding will support the conservation and restoration planning process for this species on the Qinghai-Tibet Plateau. Jayasinghe et al [17] investigated the factors influencing the expression of persistence in perennial ryegrass populations and found significant fixed effects of cultivar, endophyte, and environment and their interactions on the persistence traits of perennial ryegrass. Wu et al [18] investigated the current and future distribution of orchardgrass-suitable areas globally and found that the areas suitable for habitats increased at higher latitudes while decreasing at lower latitudes as greenhouse gas emissions increased.…”
Section: The Management and Utilization Of Traditional Grasslandsmentioning
confidence: 99%